(untitled) (Research Journal on Multi-disciplinary Issues, 2021)
Writing is an art and integral part of language teaching and learning. The present research study explores the development of writing skills especially ‘’writing essay’’ through teacher correction technique and self analysis. As action research in nature aims to test the progress of English language learners while writing an essay, this study relates to the action research. It was seen development in students writing in post test than in pre-test after analysis of the data. The students (Ss1-Ss10) were found using the words in an increased order, proper use of mechanics, and grammatically correct sentences in their writing in each test made and committed less grammatical errors in post test than in pre-test. Regarding mechanics of writing, their writing was found systematic in case of punctuation, coherence, cohesion and organization as well. The teacher correction technique and self analysis were found productive in teaching writing through action research as a whole.